HIDROCARBONETOS NO MATERIAL PARTICULADO EM SUSPENSÃO DA BAÍA DE GUANABARA: AVALIAÇÃO DO ESTADO DE CONTAMINAÇÃO - Barros, Iná; Farias, Cássia; Hamacher, Cláudia; Araújo, Michelle; Paixão, Bruna; Souza, Lays (Geochimica Brasiliensis, 2018)
Located in the center of the metropolitan region of Rio de Janeiro, and surrounded by one of the most developed regions of Brazil, Guanabara bay is one of the most degraded estuarine environments in the country, with a chronic contamination state by hydrocarbons. The present work aims to characterize the state of contamination of the particulate suspended matter (PSM) of Guanabara bay in relation to hydrocarbons. Two samplings were carried out in April 2015 and March 2016 to evaluate surface PSM along two transects sampled during complete tidal cycles in Guanabara bay. The PSM ranged from 1.76 to 61.89 mg.L-1 considering both campaigns, and significant difference between samplings or transects sampled were not observed. The C/N ratio presented median values ​​between 5 and 9 throughout the study, indicating the predominance of autochthonous organic matter mainly formed by phytoplankton. These results are expected for Guanabara bay, a highly eutrophic environment with high primary productivity. Throughout the samplings, the Σn-alc ranged from 0.00 to 35.96 μg.g-1 (median of 6.90 μg.g-1) and the ΣHA ranged from 0.23 to 1404.34 μg.g-1 (median of 35.98 μg.g-1). The Σ16 USEPA ranged from 0 to 509.21 ng.g-1 (median of 259.14 ng.g-1) and ΣHPA ranged from 25.62 to 659.57 ng.g-1 (median of 314. 35 ng.g-1). The values ​​found in the present study corroborate those observed in other recent studies in Guanabara bay and are considered significant.